السرقة العلمية وآليات مكافحتها في الفقه الإسلامي والقانون الجزائري - خنوفة, نجوى (University of Eloued جامعة الوادي, 2022)
This study is tagged with: "Scientific theft and mechanisms to combat it in Islamic theft and Algerian law", which was the main problem: "How effective are jurisprudence and legal mechanisms in combating and timiting scientific?", What I worked to answer was drawing up a dual-detective plan: I devoted the first to explaining the reality of scientific theft in terms of concept, the wisdom and wisdom of it, and the presentation of the words related to it and the summary of its most prominent images; While the second was concerned with examining its causes and depicting the damages resulting from it, and I concluded it by revealing the mechanisms used to reduce scientific theft, in an attempt by me to compare Islamic jurisprudence and Algerian law in all of the above. The research reached a number of results, the most important of which are: the effective role played by Islamic law in curbing scientific theft; By establishing an ethical system that protects against such violations, the Algerian legislator recommended a number of measures in his quest to get rid of scientific thefts.
كتاب. معهد العلوم الإسلامية. جامعة الوادي
Keywords: السرقة العلمية